The molecular signature of AML with increased ALDH activity suggests a stem cell origin - Blume, Rachel; Rempel, Eugen; Manta, Linda; Saeed, Borhan R.; Wang, Wenwen; Raffel, Simon; Ermakova, Olga; Eckstein, Volker; Trumpp, Andreas; Ho, Anthony Dick; Lutz, Christoph (Leukemia and lymphoma, 2018)
Enrichment of leukemic blasts with a stem cell phenotype correlates with poor survival in acute myeloid leukemia (AML). In this context, measurement of the stem cell marker aldehyde-dehydrogenase (ALDH) activity can distinguish poor prognosis cases with increased fractions of ALDH-positive cells (ALDH-numerous AML) and favorable outcome cases with low percentages (ALDH-rare AML). It has been shown that ALDH-numerous AML favor leukemic engraftment in xenotransplantation assays which suggests increased leukemic stem cell (LSC) potential. To test if this reflects an immature cell of origin, comparative gene-expression studies of CD34+ leukemic blasts were performed. This analysis revealed increased expression of LSC and HSC signatures in ALDH-numerous AML, whereas ALDH-rare AML were enriched for a progenitor signature. The enrichment of stemness-associated transcriptional programs suggests that ALDH-numerous AML derive from immature hematopoietic progenitors and offers an explanation for the poor prognosis and therapy resistance of this subgroup which is likely caused by inherited stem cell properties.